SISTEM iNFORMASI MUSYAWARAH PERENCANAAN PEMBANGUNAN - Yusra Mulajato; Tajuddin Abdillah; Moh Ramdhan Arif Kaluku (Diffusion: Journal of Systems and Information Technology, 2021)
YUSRA MULAJATO. A Development Planning Information System  (the principal supervisor is Tajuddin Abdillah, S.Kom, M.Cs., and the co-supervisor is Moh. Ramdhan Arif Kaluku, S.Kom, M.Kom.)Musrenbang (Musyawarah Perencanaan Pembagunan or Development Planning Consultation Forum) is a part of the government's annual forum in development planning where is management remains to experience various problems. One of the problems includes a requirement for Kelurahan (Urban Village) to submit data of Musrenbang activity result, whether softcopy or hardcopy, to Sub-district and Bappeda (Regional Development Planning Agency). Then, the Sub-district will re-submit the data to the Bappeda in which this process is believed to cause a delay in the data  processing. Also, due to data duplication is made frequently, search for Musrenbang data is time-consuming when needed.  This research aims to develop a Development Planning Concultation Forum Information System, which can be integrated into F-SKPD Information System. System development method applies prototype. Research finding reveals that the Development Planning Consultation Forum Information System can perform  an exchange data with F-SKPD Information  System. Therefore, it facilitates Kelurahan and Sub-district in managing data of Musrenbang activity result and simplifies Musrenbang process of making report as well as ease the Bappeda in searching Musrenbang data.  Keywords: Musrenbang, Prototype